FGF18 Inhibits Clear Cell Renal Cell Carcinoma Proliferation and Invasion via Regulating Epithelial-Mesenchymal Transition - Yang, Chen; Zhang, Zheyu; Ye, Fangdie; Mou, Zezhong; Chen, Xinan; Ou, Yuxi; Xu, Chenyang; Wu, Siqi; Cheng, Zhang; Hu, Jimeng; Zou, Lujia; Jiang, Haowen (Frontiers in Oncology, 2020)
Fibroblast growth factor 18 (FGF18), a member of FGF family, contributes to a broad range of biological events. The important role of overexpression of FGF18 has been identified in the progression of several types of cancers. However, the biological role of FGF18 still remains unclear on clear cell renal cell carcinoma (ccRCC), which interests us in investigating the biological functions of FGF18 in ccRCC. Our results showed that FGF18 was lowly expressed in ccRCC tissues compared to paired normal renal tissue in TCGA database and clinical cohort of Huashan Hospital, and high expression of FGF18 had a correlation with good prognosis in ccRCC patients. In addition, overexpression of FGF18 significantly inhibited the proliferation ability of ccRCC cell lines in vitro and in vivo. Gene set enrichment analysis (GSEA) identified epithelial-mesenchymal transition (EMT) involved in high FGF18 expression group of ccRCC patients in TCGA cohort, which was further validated with EMT related markers in FGF18 overexpressed ccRCC cell lines. Furthermore, FGF18 overexpression significantly inhibited PI3K/Akt pathway in ccRCC cells. Taken together, we draw to a conclusion that FGF18 is of potential value as a valuable target for ccRCC.